A Study On The Influence Of Organizational Culture And Management Style On User's Satisfaction In Organizational Buying - Omar, Akmar (2000)
Many studies have been done in industrial buying. However, they do not investigate the buying in government organizations. This study focuses on position influence on buying centers with top management styles as the moderating variable; This study investigates whether there is a relationship between customer driven culture and user satisfaction in organizational buying. If there is such a relationship, how would management style influence that relationship. A survey was conducted on the perceived culture and perceived management styles of the employees of the State of Penang government departments and their satisfaction. The result of this study shows that there is a relationship between customer driven culture and user's satisfaction.